Multicenter, prospective, comparative cohort study evaluating the efficacy and safety of alfuzosin 10 mg with regard to blood pressure in men with lower urinary tract symptoms suggestive of benign prostatic hyperplasia with or without antihypertensive med - Zhang LT (Dove Medical Press, 2015)
Li Tao Zhang,1 Sung Won Lee,2 Kwangsung Park,3 Woo Sik Chung,4 Sae Woong Kim,5 Jae Seog Hyun,6 Doo Geon Moon,7 Sang-Kuk Yang,8 Ji Kan Ryu,9 Dae Yul Yang,10 Ki Hak Moon,11 Kweon Sik Min,12 Jong Kwan Park1 1Department of Urology, Chonbuk National University, Medical School and Biomedical Research Institute and Clinical Trial Center for Medical Devices of Chonbuk National University Hospital, Jeonju; 2Department of Urology, College of Medicine, Sungkyunkwan University, Seoul; 3Department of Urology, College of Medicine, Chonnam National University, Gwangju; 4Department of Urology, College of Medicine, Ewha Woman’s University, Seoul; 5Department of Urology, College of Medicine, Catholic University, Seoul; 6Department of Urology, College of Medicine, Kyungsang National University, Jinju; 7Department of Urology, College of Medicine, Korea University, Seoul; 8Department of Urology, Chungju Hospital, College of Medicine, Konkuk University, Chungju; 9Department of Urology, College of Medicine, Inha University, Incheon; 10Department of Urology, College of Medicine, Hallym University, Seoul; 11Department of Urology, College of Medicine, Youngnam University, Daegu; 12Department of Urology, College of Medicine, Inje University, Busan, Republic of Korea Background: The objective of this study was to assess the efficacy and safety of alfuzosin 10 mg monotherapy or combined antihypertensive medication on blood pressure (BP) in patients with lower urinary tract symptoms suggestive of benign prostatic hyperplasia (BPH/LUTS) with or without antihypertensive medication.Methods: This was a 3-month, multicenter, randomized, open-label study in 335 patients aged ≥45 years with a clinical diagnosis of BPH/LUTS by medical history and clinical examination, a total International Prostatic Symptom Score (IPSS) ≥8 points, a maximum flow rate >5 mL/sec and ≤15 mL/sec, and a voided volume ≥120 mL. Eligible subjects were randomized to receive alfuzosin 10 mg as monotherapy (group 1) or alfuzosin 10 mg + antihypertensive combination therapy (group 2). Based on baseline BP and hypertensive history with or without antihypertensive medications at first medical examination, group 1 was divided into two subgroups of normotensive and untreated hypertensive patients, and group 2 into two subgroups of controlled hypertensive and uncontrolled hypertensive patients. The primary study outcomes were change in IPSS, BP, and heart rate from baseline. Secondary outcomes were change in IPSS-quality of life score, maximum flow rate, average flow rate, voided volume, and post-voided volume.Results: The overall BP change was not significantly different between groups 1 and 2 (systolic BP, P=0.825; diastolic BP, P>0.999). In patients with uncontrolled or untreated hypertension, alfuzosin 10 mg alone or combined with antihypertensive therapy significantly decreased systolic and diastolic BP. The mean difference in total IPSS and IPSS-quality of life scores from baseline between groups 1 and 2 was 0.45 (95% CI: −1.26, 2.16) and 0.12 (95% CI: −0.21, 0.45), respectively (both P>0.05). Maximum flow rate, average flow rate, voided volume, and post-voided volume at endpoint were numerically, but not significantly, changed from baseline (all P>0.05).Conclusion: This study shows that alfuzosin 10 mg is effective and well tolerated in patients with BPH/LUTS with or without antihypertensive medications. However, in patients with uncontrolled or untreated hypertension, alfuzosin 10 mg alone or in combination with antihypertensive medication appears to decrease systolic and diastolic BP, and these patients should be warned about a decrease in BP on initiation of therapy. Keywords: alfuzosin, lower urinary tract symptoms, benign prostatic hyperplasia, antihypertensive medication, blood pressureA Letter to the Editor has been received and published for this article.